The Error Analysis of Writing Recount Text at Third Semester Students of English Education Department in Academic Year 2019/2020 - Adib Ahmada (Universitas Cokroaminoto Palopo, 2020)
The researcher as the lecturer at the Third Semester Students in English Education Department, Faculty of Education and Teacher Training, Islamic Institute of Darussalam Blokagung Banyuwangi in academic year 2019/2020 found the problem in students’ understanding in writing recount text. Although The students had got the material about writing recount text in the previous semester, they were still got difficulties on it. Here, the researcher interested to analyze students’ error in writing recount text deeply. The purpose of this research was to find out the students’ problem in writing recount text, so that the researcher can decide the appropriate method in teaching writing in the third Semester. The researcher used descriptive qualitative method. The data was taken from the students’ writing test in third semester of English education department that consist of 30 students. To collect the data, first, asking the students to write a recount text with the topic given. Second, analyze the result of students’ task. Third, Finding and marking the errors in students’ writing task. Fourth, divide the errors based on the types of errors. The result of the test had been analyzed and then classified into four types of the errors, those were mis-formation, omission, addition and mis-ordering. Based on the finding in this research, there were 70 errors made by the students in writing recount text. The errors were 13 errors or 15.71% in mis-formation, 16 errors or 22.85% at omission, 37 errors or 52.85% at addition and 6 or 8.57% errors in mis-ordering. From the result of the data, it could be concluded that students still find difficulties in writing recount text. It could be seen from the errors they made. The errors cover mis-formation, omission, addition and mis-ordering.